The Civilization and Thought of Islam During The Era of the Three Great Islamic Empires: A Historical Study - Prayogi, Arditya; Arisandi, Devy; Cahyo Kurniawan, Pratomo (Al Irsyad: Jurnal Studi Islam, 2023)
The history of Islam is important to study in order to achieve greatness; Islamic civilization advanced rapidly during the Abbasid, Ottoman, Safavid, and Mughal periods in fields of science, governance, culture, and education. This article discusses the formation, progress, and decline of the civilizations of the three great Islamic empires: Ottoman, Safavid, and Mughal. The writing uses a qualitative descriptive approach with a literature study method. Research Findings: The Ottoman, Safavid, and Mughal Sultanates were three major Islamic empires that flourished between the 13th and 18th centuries. The Ottomans reached their peak under Muhammad Al-Fatih and Suleiman the Magnificent, marked by dominant military and cultural power. The Safavids emerged from a Shia Sufi order and thrived under Abbas I through religious tolerance and artistic development. The Mughal Empire in India, founded by Babur, experienced its golden age during Akbar’s reign, known for tolerance, education, and the arts. Despite eventual decline due to internal and external conflicts, their architectural and cultural legacies remain significant today. Conclusion: The greatness of the three Islamic empires of the 17th century was formed through historical processes, achieved progress, but ultimately declined due to various internal and external factors.